Water-based extraction methods of Moringa oleifera leaves for xanthine oxidase inhibitory activity / Mohamad Daniel Mohamad Basri ... [ et al.] - Mohamad Basri, Mohamad Daniel Mohamad Basri; Mad Nordin, Mariam Firdhaus; Mohamad Abdul Wahab, Izzati; Mohd Amir, Siti Nur Khairunisa; Mokhtar, Norrashidah (Universiti Teknologi MARA, 2020)
The purpose of this study is to investigate the medicinal properties of Moringa oleifera (M. oleifera) leaves towards xanthine oxidase inhibitory activity by using water-based extraction methods such as boiling extraction, subcritical water extraction (SWE) and ultrasonic-assisted extraction (UAE). Boiling extraction is chosen as the control method in this study due to its commonly used in the industry. Water based extraction is investigated to determine if it can replace the conventional extraction method which uses organic solvent and time consuming. Temperature and time were investigated using central composite design (CCD) for maximum xanthine oxidase inhibitory activity in SWE and UAE. The boiling extraction is operated at fixed temperature of 100 °C while SWE is utilised at temperature of 100 to 180 °C and UAE at 30 to 60 °C with same time within 10 to 30 min. These variables are used to determine optimum condition on each method for xanthine oxidase inhibitory activity of M. oleifera leaves, then compared with the control method to identify ideal method of extraction. Thus, SWE (69.65 ± 0.1 %) at 180 °C and 20 min is the ideal method compared to UAE (48.89 ± 0.3 %) at 60 °C and 30 min and boiling extraction (41.88 ± 0.1 %) at 100 °C and 20 min due to higher percentage of xanthine oxidase inhibitory activity obtained on M. oleifera leaves. The findings of this study show that SWE offer better alternative for M. Oleifera extraction towards xanthine oxidase inhibitory compares to other methods.